Role and Risk Factors involved at Middle Level Management in Sericulture in Andhra Pradesh - S. V. Seshagiri; C. Rajagopal Reddy; P. Vara Prasad; A.K. Goel; P.J. Raju (Journal of Agricultural Extension Management, 2025)
The services offered by the Department of Sericulture are mainly meant for the welfare of the entrepreneurs of On-farm and Non-farm sectors who directly and indirectly depend on the enterprise and for the overall development of the sericulture industry. For the purpose of organization and development of the industry, the Department of Sericulture has established different units in On-fa.rm and Non-farm sectors and each of the units is looked after by middle level managers. This study is mainly on the role of the middle level managers, their performance in organizational development, production and marketing systems and the risk factors involved in their jurisdiction. The study revealed that the main function being extension of technical guidance and providing other facilities to farmers, the managers have a role to play for the welfare of the Sericulturists. It also found that the unit manager’s job is quite challenging in implementation of various schemes and also with a financial risk. Further the study also focused on the recommendations I suggestions for following a strategic approach in effective running of the units